Comparative Analysis of Bacterial Conjunctivitis in the Adult and Pediatric Inpatient vs. Outpatient Population - Adela Voinescu; Corina Musuroi; Monica Licker; Delia Muntean; Silvia-Ioana Musuroi; Luminita Mirela Baditoiu; Dorina Dugaesescu; Romanita Jumanca; Mihnea Munteanu; Andrei Cosnita (Microorganisms)
The etiology and resistance pattern of bacterial conjunctivitis varies depending on the patient’s care setting and age. A retrospective, observational study was conducted in a tertiary care teaching hospital. A total of 126 patients—76 adults and 50 children—diagnosed with conjunctival infection during inpatient or ambulatory care were analyzed. In the samples of adult patients, isolates were represented by Gram-positive cocci (57.7%; Staphylococcus spp., S. pneumoniae) followed by Enterobacterales (17.97%; P. mirabilis, E. coli, Klebsiella spp.), and non-fermenters (7.69%; Pseudomonas spp., A. baumannii). Multidrug-resistant (52.17%) and extensively drug-resistant (21.73%) pathogens (predominantly Gram-negative bacilli) were identified in conjunctival swabs of hospitalized adult patients. The main isolates (55.77%) identified in children’s conjunctival swabs belonged to S. aureus, H. influenzae, and S. pneumoniae, followed by Enterobacterales (19.22%; E. coli, P. mirabilis, M. morganii) and fungi (3.48%). Methicillin-resistant S. aureus (35.71%) and extended-spectrum beta-lactamase-producing K. pneumoniae (8.7%) were identified in the pediatric subgroup of patients. In critically ill adult patients assisted in the intensive care or burn functional units, bacterial conjunctivitis followed the pattern of infections and antimicrobial resistance specific to these categories of patients. In the case of hospitalized children, conjunctivitis was an integral part of the age-related pathology.